Doses de inoculante e estirpes de Azospirillum brasilense associadas à adubação nitrogenada na cultura do milho - Pinto Junior, Artur Soares (2013)
This study aimed to evaluate under field conditions in different areas of southern Brazil, the effect associated with mineral fertilizers and different dosages of inoculant formulated from the strains Ab-V5, V6 and Ab-Ab-V7 of Azospirillum brasilense. The experimental design was randomized blocks with four blocks and ten treatments. The treatments were formed by the doses of 0, 60 and ha-1 of nitrogen without seed inoculation dose to 120 kg and 60 kg ha-1 nitrogen + individual inoculation and associated strains of Ab-V5, V6 and Ab-Ab -V7. Biometric evaluations were performed during the stage of eight mature leaves (V8), as well as assessments of components of production and productivity at the end of the crop cycle. Levels of N, P and K leaves in early female flowering were also evaluated as well, the levels of these nutrients in grains. The results indicate that regardless of the area evaluated, the use of inoculant base of A. brasilense associated with the dose of 60 kg ha-1 of nitrogen results in increases in growth, development and yield of corn